FAKTOR YANG MEMPENGARUHI KUNJUNGAN MASA NIFAS DI BPM YUNI WATI.KOTA PEKANBARU - Lisviarose; Komaria Susanti; Nafila Darhesta (Jurnal Doppler, 2022)
ABSTRACT The postpartum period is a vulnerable period for mothers, about 60% of maternal deaths in Indonesia occur after childbirth and almost 50% of deaths during the puerperium occur in the first 24 hours after delivery, including complications during the puerperium. Problems during the puerperium will have an impact on the welfare of the baby born, because the baby will not get maximum care from his mother. The purpose of this study was to determine the factors that influence postpartum visits at the independent practice midwife "Y" Sidomulyo Barat Village, Tampan District, Pekanbaru City. The research method used in this research is quantitative with analytical design through a cross sectional approach. The population in this study were all postpartum mothers at BPM Yuni Wati Amelia, Amd. Keb. Pekanbaru from December 2021 - January 2022 as many as 34 people with a total sample of 34 respondents and sampling using the Total Sampling technique. Analysis of the data used is chi square with a limit of 95% significance degree (? = 0.05). Based on the results of the study, there is an influence between knowledge on postpartum visits with p value = 0.002 or p value <0.05, there is an influence between attitudes towards postpartum visits with p value = 0.002 or p value <0.05, there is an influence between family support for postpartum visits with p value = 0.001 or p value <0.05. From the results of this study, it is expected for BPM to be able to increase the role of midwives in providing midwifery care to postpartum mothers about postpartum visits and for postpartum mothers to add insight and become input for postpartum mothers to visit postpartum.